PENGUATAN SDM DAN TATA KELOLA KELEMBAGAAN POKDARWIS DEWI RENGGANIS DI DESA WISATA GUYANGAN, KRUCIL, KABUPATEN PROBOLINGGO - Pandu Hutama; Didik Eko Julianto; Panca Oktawirani; Akhmad Toha; I Ketut Mastika; Wheny Khristianto; Dwi Windradini (Universitas Pahlawan Tuanku Tambusai, 2023)
Guyangan Village is one the village that located in strategic position by its diversity on tourism potencies and wide spread of livelihood in agriculture, horticulture and plantation. In 2021, this village have awarded as the one of tourism village by 29 villages in Probolinggo Regency. The harvest of agriculture of rice field, corn, and horticulture such cubic, tomato and potatoes, as well as coffee, durian and dairy cows and beef cattle. By its wide spread potencies of nature to be attract by visitors, especially of Batu Pertapaan Sites, Sendang Biru Waterfall, Jaran Goyang Waterfall, Dewi Rengganis Waterfall, Gligir Waterfall, Watulesung Waterfall and Live Garden. This research aims to develop of skill of hospitality community of Dewi Rengganis in Seventh Charms and also Management of Tourism Village. The methodology used the Socialization of Seventh Charms, Tutorial method and service to the visitors, Discussion method in understanding and experience of local community and also Evaluation method through hospitality community of Dewi Rengganis